Inline fouling mitigation during food processing: a sustainable novel solution. (September 2017) - Nchari, Luanga; Edge, Charles; Shafiq, Mohammed
Abstract: Fouling within the food industry has an impact on both capital and operation costs. There is a great demand for cost effective and sustainable antifouling solutions. An increase in internal fouling results in poor thermal efficiency during food processing. This is coupled with poor heat and mass transfer local to the metal surface of designed heat exchangers, pipes and other equipment. Internal fouling could also potentially increase unwanted fluid flow pressure due to restricted flow. [1, 2] It is demonstrated in this work, how fouling is mitigated with ultrasound non-invasively during pilot scale production. When using a plate heat exchanger set-point temperature of 140°C, 128°C and 138°C was achieved without and with an attached ultrasonic transducer respectively. The duration for complete fouling of a tubular heat exchanger increased from 10 to 25 hours with ultrasonic transducers. The presence of ultrasound reduces the carbon footprint owing to substantially reduced fouling.